CFS in Children and Adolescent: Ten Years of Retrospective Clinical Evaluation - Irene Elgen; Omar Hikmat; Tora N. Aspevik; Ellen Merete Hagen (Hindawi Limited, 2013)
Aim. To estimate number of children being diagnosed with chronic fatigue syndrome (CFS). Methods. For a period of 10 years (2002-2011) data from children being referred for fatigue symptoms were collected retrospectively. Results. Thirty-seven children were referred. Four were excluded due to incorrect coding. Six (18%) patients received other diagnoses at the end of evaluation time. Of the 27 who received the diagnosis G93.3, four had a previous chronic illness, while 23 patients were previously healthy. All patients reported onset of fatigue symptom in relation to an infection, and all tested positive for IgG to either Epstein-Barr virus, cytomegalovirus or borrelia, indicating previous infection. There were 16 (59%) boys among the 27 patients. The mean age at the debut of fatigue symptoms was 141 months (SD 30) for boys and 136 months (SD 31) for girls, respectively. Being underweight, defined as BMI < 17.5, was found in 12 (44%) patients. Conclusion. An increasing number of children and adolescents are evaluated for CFS. The clinical assessment of children and adolescents with possible CFS need systematically evaluation. Nutritional status, possible eating disorder, and psychosocial issues need to be addressed and evaluated carefully. A multidisciplinary approach is essential when assessing CFS in children and adolescents. There is a need for European guidelines.